Integration of the project “ Information Technology in Computer-Assisted Translation of Croatian and in e-Language Learning” into curriculum - Seljan, Sanja; Pavlović, Nataša (2008)
This paper aims to describe the integration of the project for an under-resourced language, Croatian, into curriculum at two departments at the Faculty of Humanities and Social Sciences, University of Zagreb, especially for students of Information Sciences and English. In particular, we would like to share our plans to incorporate the three-year project entitled “ Information Technology in Computer-Assisted Translation of Croatian and in e-Language Learning” into the translator training curriculum. The project has started as a response to changes at the national level and the need for integration into European surroundings. The basic aim of the project is to investigate and to develop, as much as possible, resources and tools for CAT and for eLL for Croatian, according to the experience of new EU member states and in accordance with EU standards.
Projekt MZOS
ENG